Manajemen Perkembangbiakan dalam Usaha Penangkaran Rusa (Cervus spp.) Ditinjau dari Aspek Perilakunya - Sambas Basuni (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
The success of deer (Cems spp.) breeding in captivity requires understanding of the basic reproductive characteristics of hinds and stags and factors affecting their performance.Birth-pulse breeding season is less pronounced in tropical regions than in artic and temperate regions. However, most ungulate species in semi-arid and arid tropical regions do show seasonality in breeding (birth-pulse breeding season) and there is also evidence that certain ungulate species,especially from the family Bovidae and Cervidae, in humid tropical regions tend to have more or less distinct breeding season. For example, Cervus timorensis has a breeding season in July - September and an onset of calving in May - June with the length of gestation period of 267 - 284 days.Little is known about the reproductive characteristics of Cems unicolor, but information about Cervus elophus in New Zealand possibly can be used as a comparative reference.The management of stags at mating is a crucial factor in reproduction and much of it is related to their competitive behaviour. When more than one stag is running with a group of hinds, a hierarchy will be established and one of them, usually the largest, becomes dominant and can control a large harem. With or without antlers, stags become extremely belligerent and dangerous to handle during the rut, so it is wise to introduce them into mating groups well before mating starts. Early introduction may result in unnecessary exhaustion of stags before mating actually starts, because stags reduce their feeding activities dramatically while defending a harem.